The Communicative English Classroom: A Fascinating Quest - Nieto María Claudia (Profile: Issues in Teachers' Professional Development)
In the present article I describe my vision of what an English classroom should be like. For me, the vision is that of creating a communicative classroom. I define it as the space where participants (both learners and teachers) seek the learning of a foreign language bearing in mind specific objectives. I then point out its main characteristics. I conclude that the communicative classroom may facilitate learning because of its many advantages.